History of Ukrainian Philosophy: Teaching and Evaluation Methodology - Sergii Rudenko (International Society of Philosophy and Cosmology, 2018)
This article presents the author's methodology for teaching the History of Ukrainian Philosophy for students of the Taras Shevchenko National University of Kyiv as well as a methodology for evaluating learning outcomes based on a competence approach. The author has formulated eight key competences in the field of History of Ukrainian Philosophy, which are used to formulate the content model of the training course, as well as evaluation the results of students' study of the History of Ukrainian Philosophy. The Evaluation principles are represented through the two groups. The first group describe historiographical abilities whereas the second one reflects abilities concerning the rational reconstruction. Combination of these two groups of competencies makes the Evaluation Methodology clear, flexible and representative. The paper proposes an expanded content model of the course on History of Ukrainian Philosophy, which is based on author's research in the field of historiography of Ukrainian philosophy and methodology of the study of the History of Ukrainian philosophy.